Parental knowledge gaps and barriers for children receiving human papillomavirus vaccine in the Rio Grande Valley of Texas. Issue 7 (3rd August 2019) - Victory, Melissa; Do, Thuy Quynh N.; Kuo, Yong-Fang; Rodriguez, Ana M.
ABSTRACT: Purpose : Despite its availability for more than a decade, the human papillomavirus (HPV) vaccine has low uptake in Texas (49%). The objective of this study was to understand parental knowledge and attitudes about HPV and the HPV vaccine as well as child experience with the HPV vaccine among a medically underserved, economically disadvantaged population. Methods : As part of a Cancer Prevention Research Institute of Texas-funded project to improve HPV vaccination rates, we surveyed parents / guardians of 4 th –12 th graders (ages 9–17) in the Rio Grande City Consolidated Independent School District (RGCCISD). Descriptive statistics were used to describe parents' knowledge and attitude and children's vaccine experience. Results : Of the 7, 055 surveys distributed, 622 (8.8%) were returned. About 84% of the respondents were female. About 57.1% of the parents /guardians had female RGCCISD students with a mean age of 11.7 ± 1.8 years. Overall, 43.9% reported receiving a healthcare provider recommendation and 32.5% had their child vaccinated. Higher percentages were reported if the respondent was female and had a female child aged ≥15 years old. Among survey respondents, 28.2% reported their child initiated the HPV vaccine and 18.8% completed the series. Barriers of uptake included work / school schedule conflicts and no healthcare provider recommendation. Conclusions : There are still prominent gaps in parents' and students' complete understanding of HPV vaccination, gender preferences for vaccination, and provider recommendations. Future interventions must target men and minority populations in order to increase knowledge and awareness about HPV, the HPV vaccine, and HPV-associated cancers.